Development of gemcitabine-modified miRNA mimics as cancer therapeutics for pancreatic ductal adenocarcinoma - John G. Yuen; Ga-Ram Hwang; Andrew Fesler; Erick Intriago; Amartya Pal; Anushka Ojha; Jingfang Ju (Molecular Therapy: Oncology)
Despite the recent advancement in diagnosis and therapy, pancreatic ductal adenocarcinoma (PDAC), the most common type of pancreatic cancer, is still the most lethal cancer with a low five-year survival rate. There is an urgent need to develop new therapies to address this issue. In this study, we developed a treatment strategy by modifying tumor suppressor miRNAs, miR-15a and miR-194, with the chemotherapeutic gemcitabine (Gem) to create Gem-modified mimics, Gem-miR-15a and Gem-miR-194, respectively. In a panel of PDAC cell lines, we found that Gem-miR-15a and Gem-miR-194 induce cell-cycle arrest and apoptosis, and these mimics are potent inhibitors with IC50 values up to several hundred fold less than their native counterparts or Gem alone. Furthermore, we found that Gem-miR-15a and Gem-miR-194 retained miRNA function by downregulating the expression of several key targets including WEE1, CHK1, BMI1, and YAP1 for Gem-miR-15a, and FOXA1 for Gem-miR-194. We also found that our Gem-modified miRNA mimics exhibit an enhanced efficacy compared to Gem in patient-derived PDAC organoids. Furthermore, we observed that Gem-miR-15a significantly inhibits PDAC tumor growth in vivo without observing any noticeable signs of toxicity. Overall, our results demonstrate the therapeutic potential of Gem-modified miRNAs as a treatment strategy for PDAC.